Pengajaran Dialek Daerah dalam Pengajaran BIPA Penting atau Tidak Penting? - Wiannastiti, Melania (Bina Nusantara University, 2010)
Dialect defined as a language variation in which it is different in pronunciation, structure and vocabularies from the certain standard culture and language becomes an interesting issue in teaching Bahasa Indonesia for non-native Indonesian. It is because every part of Indonesia where Bahasa Indonesia is used as the spoken language has different dialect. Non Bahasa Indonesia speakers learning Bahasa Indonesia is determined to pass a certain level when they are able to communicate sucesfully in Bahasa Indonesia with its native speakers. However, in reality some of them face some problems to communicate directly with native speaker since the native speakers use certain dialects which is different from the standard Bahasa Indonesia. Non-native Bahasa Indonesia learners do not understand because the different words, different grammar and abbreviations. This paper is discussing about the advantages and disadvantages teaching dialect in teaching Bahasa Indonesia for Bahasa Indonesia learners and some suggestions whether it is necessary to be taught in teaching Bahasa Indonesia for foreigners or not.